Competitive Interactions Between Microbial Siderophores and Humic-Like Binding Sites in European Shelf Sea Waters - Gledhill, Martha; Zhu, Kechen; Rusiecka, Dagmara; Achterberg, Eric P. (Frontiers in Marine Science, 2022)
Siderophores are low molecular weight high affinity iron chelates found at low concentrations in seawater. In this study we determined the total concentrations and identities of siderophores in extracts isolated from a shelf sea environment on the Northwest European shelf by high performance liquid chromatography coupled to high resolution inductively coupled plasma mass spectrometry (ICP-MS) in parallel to high resolution electrospray ionisation mass spectrometry (ESI-MS). We identified a total of 24 different siderophores in our samples via metal isotope profiling of masses detected by ESI-MS. Twenty three of the identified siderophores could be assigned to three siderophore families – ferrioxamines, amphibactins and marinobactins. In contrast, only 12 peaks could be resolved in iron chromatograms obtained via ICP-MS analysis. Comparison of results obtained by the two mass spectrometry detectors showed that neither method was able to detect and identify all siderophores present in the samples on its own. We assessed the impact of our observed total siderophore concentrations on iron speciation by calculating the distribution of iron species as a function of total siderophore concentrations at different iron concentrations representative of our study area. We considered competition for iron between siderophores, a humic like dissolved organic matter (DOM) fraction and hydroxide ions by combining an ion-pair model with a non-ideal competitive interaction (NICA)-Donnan model. We found that the overall impact of siderophores on iron biogeochemistry is low at concentrations of siderophore <100 pmol L-1, and that the dominant iron species present at siderophore concentrations of the order of a few tens of pmol L-1 will be iron bound to the humic like DOM fraction. Furthermore the heterogeneity of binding sites in the humic like DOM fraction means that other binding sites present in organic matter could be effective competitors for siderophores, especially at low iron concentrations. Our findings highlight the importance of considering binding site heterogeneity when considering the influence of different iron binding groups on iron speciation in the marine environment.